Promoting Students’ Academic Speaking Skills Through Project Report Presentation - Ida Bagus Nyoman Mantra; Nengah Dwi Handayani; I Nyoman Suwandi; Wayan Maba (International Journal of Linguistics and Discourse Analytics, 2022)
Speaking skill is the art of talking that a person has to express what is being thought and felt to convey a spoken message. Having good speaking is highly important for us to create a harmonious and balanced social life. Students are expected to have good speaking skills to be able to communicate academically in addition to being social beings. This study made use of a classroom action research design with two cycles of learning activities to improve students' speaking skills through project report presentation strategies. Data were collected through pre-test, post-test, and questionnaire. Based on the data analysis, it was found that the speaking skills of the students increased from the first and second cycles when compared to the results of the pre-test. Therefore, the project report presentation strategy is considered very effective for learning speaking skills. This study implies that teachers should consider using project report presentation strategy to improve students' speaking skills